2020
DOI: 10.5194/gmd-13-4271-2020
|View full text |Cite
|
Sign up to set email alerts
|

Can machine learning improve the model representation of turbulent kinetic energy dissipation rate in the boundary layer for complex terrain?

Abstract: Abstract. Current turbulence parameterizations in numerical weather prediction models at the mesoscale assume a local equilibrium between production and dissipation of turbulence. As this assumption does not hold at fine horizontal resolutions, improved ways to represent turbulent kinetic energy (TKE) dissipation rate (ϵ) are needed. Here, we use a 6-week data set of turbulence measurements from 184 sonic anemometers in complex terrain at the Perdigão field campaign to suggest improved representations of dissi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…A linear regression fit minimizes the error of the dependent variable from the linear fit. This inevitably gives more weight in reducing the errors at higher TKE values than at lower TKE values where the majority of the points were located, as noted by Bonin et al [47] and Bodini et al [50]. Since the TKE values can range two orders of magnitude, this could lead to a biased regression and lower values.…”
Section: Turbulent Kinetic Energy (Tke) Validationmentioning
confidence: 97%
“…A linear regression fit minimizes the error of the dependent variable from the linear fit. This inevitably gives more weight in reducing the errors at higher TKE values than at lower TKE values where the majority of the points were located, as noted by Bonin et al [47] and Bodini et al [50]. Since the TKE values can range two orders of magnitude, this could lead to a biased regression and lower values.…”
Section: Turbulent Kinetic Energy (Tke) Validationmentioning
confidence: 97%
“…Several papers were also recently published on the topic of emulating different parts of NWP models by machine learning [31][32][33][34]. Authors are using either benchmark solutions to provide reliable estimates of examined algorithms, or using observational data from special campaigns to train models on real and accurate data.…”
Section: Atmospheric Physics and Processesmentioning
confidence: 99%
“…Using a gradient Richardson number is difficult because of the effect of terrain-induced flow speedup over the ridge affecting the shear terms (Menke et al, 2019). Bodini et al (2020) calculated the Obukhov length for Perdigão and found that it was not very powerful in predicting dissipation rate. Despite this, the Obukhov length is still useful for selecting stable and unstable case studies.…”
Section: Overview Of the Perdigão Campaignmentioning
confidence: 99%